Asymmetric Collusion and Merger Policy - Mattias Ganslandt; Lars Persson; Helder Vasconcelos (Research Institute of Industrial Economics (IFN), 2007)
In their merger control, EU and the US have considered symmetric size distribution (cost structure) of firms to be a factor potentially leading to collusion. We show that forbidding mergers leading to symmetric market structures can induce mergers leading to asymmetric market structures with higher risk of collusion, when firms face indivisible costs of collusion. In particular, we show that if the rule determining the collusive outcome has the property that the large (efficient) firm benefits sufficiently more from collusion when industry asymmetries increase, collusion can become more likely when firms are moderately asymmetric.
Keywords: D43; L41; 330; Collusion; Cost Asymmetries; Merger Policy; Fusionskontrolle; Kartell; Wettbewerbsbeschränkung; Kostenstruktur; Theorie